Reforms in the civil services - Saurabh, Sameera (Yojana)
Civil services is essential for the functioning of the government. The civil services has long been regarded as the steel frame of administration in India from colonial days. The colonial legacy of civil service is continuing in this fast changing era of globalisation. it is in this context that civil service reform forms a quintessential part of good governance. A rethinking and a reorientation are needed in the civil for effective service delivery. - Reproduced
Keywords: Civil service reforms, Good governance, Public Administration